2006
DOI: 10.1515/znb-2006-0101
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure and Ligand Mobility in Solution of cis-Dimethyl-bis(trimethylphosphine)gold(III) Complexes

Abstract: Complexes [Me 2 Au(PMe 3 ) 2 ] + X − with X = I and ClO 4 have been prepared by several conventional routes in good yields. The products are thermally stable and decompose above 130 • C with reductive elimination of ethane. The two salts crystallize as isomorphous orthorhombic dichloromethane solvates. The cations have the cis-configuration based on a crystallographically imposed C 2v symmetry. Owing to the trans influence of the tertiary phosphine ligands the Au-C bonds are significantly shorter than in stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…From ESI‐MS analysis, no formation of the Cyanex 923 tetramer or polymer complex with Li was detected. A search of the Cambridge Structural Database showed that lithium is generally four‐coordinated with triphenylphosphine oxide in Tetrahedron (T d ) geometry, for example, tetrakis(Triphenylphosphine oxide)‐lithium bis(iodo)‐gold (CCDC 606391), tetrakis(Triphenylphosphine oxide)‐lithium bromide(CCDC 112351) . The three‐coordinated Li complex with Cyanex 923 may result from steric effect due to the long alkyl chain of Cyanex 923.…”
Section: Esi‐ms Analysismentioning
confidence: 99%
“…From ESI‐MS analysis, no formation of the Cyanex 923 tetramer or polymer complex with Li was detected. A search of the Cambridge Structural Database showed that lithium is generally four‐coordinated with triphenylphosphine oxide in Tetrahedron (T d ) geometry, for example, tetrakis(Triphenylphosphine oxide)‐lithium bis(iodo)‐gold (CCDC 606391), tetrakis(Triphenylphosphine oxide)‐lithium bromide(CCDC 112351) . The three‐coordinated Li complex with Cyanex 923 may result from steric effect due to the long alkyl chain of Cyanex 923.…”
Section: Esi‐ms Analysismentioning
confidence: 99%
“…The guest complex formed in the reaction of 3-I was consistent with bis­(trimethylphosphine) gold cation 9 ⊂ 1 , which was verified by encapsulation of independently synthesized 9 (eq ). …”
Section: Influence Of Spectator Ligandsmentioning
confidence: 99%